Probing the Single Key Amino Acid Responsible for the Novel Catalytic Function of ent-Kaurene Oxidase Supported by NADPH-Cytochrome P450 Reductases in Tripterygium wilfordii - Su, Ping; Guan, Hongyu; Zhang, Yifeng; Wang, Xing; Gao, Linhui; Zhao, Yujun; Hu, Tianyuan; Zhou, Jiawei; Ma, Baowei; Tu, Lichan; Tong, Yuru; Huang, Luqi; et al. (Frontiers in Plant Science, 2017)
Tripterygium wilfordii produces not only ent-kaurene, which is an intermediate of gibberellin biosynthesis in flowering plants, but also 16α-hydroxy-ent-kaurane, whose physiological role has not been characterized. The two compounds are biosynthesized from the universal diterpenoid precursor (E,E,E)-geranylgeranyl diphosphate (GGPP) by diterpene synthases, which have been discovered and functionally characterized in T. wilfordii. Here, we described the functional characterization of four cytochrome P450 reductases (TwCPR) and one ent-kaurene oxidase (TwKO). Four TwCPRs were found to have relatively ubiquitous expression in T. wilfordii root, stem, leaf, and flower tissues. Co-expression of both a TwCPR and TwKO in yeast showed that TwCPR3 has a slightly better activity for providing the electrons required for these reactions, indicating that TwCPR3 is more suitable for use in the functional analysis of other cytochrome P450 monooxygenases. TwKO catalyzed the three-step oxidation of the C4α methyl of the tetracyclic diterpene intermediate ent-kaurene to form ent-kaurenoic acid as an early step in gibberellin (GA) biosynthesis. Notably, TwKO could also convert 16α-hydroxy-ent-kaurane to 16α-hydroxy-ent-kauranoic acid, indicating an important function of 16α-hydroxy-ent-kaurane in the anti-HIV principle tripterifordin biosynthetic pathway in planta. Homology modelling and molecular docking were used to investigate the unknown crucial active amino acid residue involved in the catalytic reaction of TwKO, and one key residue (Leu387) contributed to the formation of 16α-hydroxy-ent-kauranoic acid, most likely by forming hydrogen bonds with the hydroxyl group (-OH) of 16α-hydroxy-ent-kaurane, which laid the basis for further investigation of the multifunctional nature of KO catalysis. Also, our findings paved the way for the complete biosynthesis of the anti-HIV principle tripterifordin.